PENGARUH KOMBINASI PAKAN KOMERSIAL DENGAN DAUN KANGKUNG AIR (Ipomoea aquatica) TERHADAP PERTUMBUHAN IKAN MAS (Cyprinus carpio) - Sultan Hamdi MT; Ayu Adhita Damayanti; Dewi Putri Lestari (JURNAL PERIKANAN TROPIS, 2021)
This study aimed to analyze the effect of commercial feed combination with water spinach leaves (Ipomoea aquatica) at different ratios on the growth of common carp (Cyprinus carpio). This research was conducted for 35 days, located in Seteluk Atas Village, Seteluk District, West Sumbawa Regency. The common carp seeds used were 5-7 cm in size from one brood. The container used was 16 liter in size with a density of 10 fish / treatment. The method used in this study was an experimental method using a completely randomized design (CRD) with five treatments and three replications, namely, P1: 100% commercial feed (control), P2: commercial feed + water spinach leaves (1+1), P3: commercial feed + water spinach leaves (1+2), P4: commercial feed + water spinach leaves (1+3), P5: 100% water spinach leaves. The data obtained were then calculated and analyzed by using analysis of variance (ANOVA). The results of this study indicated that the use of commercial feed combination with water spinach leaves can affect growth, feed efficiency and feed conversion of common carp but did not affect the survival of common carp. Provision of 100% commercial feed (P1) and combination of commercial feed with water spinach leaves at a ratio of 1:2 (P3) had the same effect in increasing the growth of common carp, namely 1.17 g and 1.11 g, respectively.